Воспоминания операторов ЗТШ о К.К. Чуваеве - Суница, Г.; Таран, А.; Стадниченко, Б.; Семенов, Г.; Зубко , Н. (Известия Крымской астрофизической обсерватории, 2008)
Воспоминания операторов ЗТШ о К.К. Чуваеве